2019
DOI: 10.1287/mnsc.2017.2935
|View full text |Cite
|
Sign up to set email alerts
|

Private Ownership and the Cost of Public Debt: Evidence from the Bond Market

Abstract: A number of studies have examined the effect of public and private ownership on the cost of debt and concluded that the cost of debt of privately owned firms is higher, driven mainly by the poorer information environment in which these firms operate. We extend this strand of research in two ways. First, we identify and empirically establish the mechanisms that bring about a higher cost of debt to privately owned firms—namely, the limited access that these firms have to the equity capital market, their high rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…Furthermore, Badertscher et al [27] show that companies with more independent board structure and more effective board approach have more market liquidity compared to other companies. In fact, companies with higher score in terms of corporate governance quality experience lower ask-bid spread and higher different share supplied and demanded.…”
Section: Director Board Characteristics and Cost Of Debtmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Badertscher et al [27] show that companies with more independent board structure and more effective board approach have more market liquidity compared to other companies. In fact, companies with higher score in terms of corporate governance quality experience lower ask-bid spread and higher different share supplied and demanded.…”
Section: Director Board Characteristics and Cost Of Debtmentioning
confidence: 99%
“…Furthermore, the theoretical and empirical studies about corporate governance have suggested that the ownership structure is a crucial determinant of the governance practices effectiveness [28] and [27]. According to Shleifer and Vishny [28], ownership concentration increases control over managers.…”
Section: Ownership Structure and Cost Of Debtmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, information from rating agencies could lead to increased investor demand for information from management because investors are trying to better interpret the rating agency disclosures or perhaps predict the rating itself.Our tests control for whether a firm is private, which means it lacks publicly-traded equity.In this test, as we restrict this sample to firms with available data in Compustat North America, our private firms of interest do issue public debt, which requires them to file typical SEC disclosures, like 10-Ks and 10-Qs (the source of Compustat's information). These private firms have been the focus of some studies, such asKatz (2009) andBadertscher et al (2019). Even though they file with the SEC, this sample of private firms continue to have weaker information environments than typical public firms because they may have less media and sell-side analyst coverage, and by definition they don't have a public stock price that aggregates value relevant information.…”
mentioning
confidence: 99%